Compressive Strength of Palm Oil Lightweight Aggregate Concrete Containing Industrial Waste as Partial Sand Replacement - Khairunisa, Muthusamy; Nur Farah Aziera, Jamaludin; Mohd Faizal, Md Jaafar; Ahmed Mokhtar Albshir, Budiea; Mohamed A., Ismail (Trans Tech Publications Ltd, Switzerland, 2022)
Palm oil fuel ash (POFA) and palm oil clinker (POC) are by-products from palm oil mill which disposed as environmental polluting wastes. Excessive sand mining activity by sand traders for the widely used concrete production, harms the river’s ecosystem. Success in discovering alternative material that can function as partial sand replacement for concrete production would reduce the dependency on natural sand supply. This research investigates the effect of POFA as a partial fine aggregate substitute on the workability and compressive strength of palm oil clinker lightweight aggregate concrete. Five mixes have been prepared by integrating diverse percentage of POFA ranging from 0, 5, 10, 15 and 20 as fine aggregate substitute by weight of sand. Then, concrete mixes were subjected to slump test and compressive strength test. The outcomes have shown the combination of 5% POFA in this lightweight aggregate concrete produces concrete with the targeted strength and has the potential to be used for structural application. Utilization of POFA in concrete would save the consumption of river sand and contribute to sustainable environment.